Observation and determination of periodontal tissue profile using optical coherence tomography. (24th October 2017) - Kakizaki, S.; Aoki, A.; Tsubokawa, M.; Lin, T.; Mizutani, K.; Koshy, G.; Sadr, A.; Oda, S.; Sumi, Y.; Izumi, Y.
Abstract : Background and Objective: Diagnosis is a crucial step in periodontal treatment. The aim of this study was to evaluate the effectiveness of optical coherence tomography (OCT) for observation and determination of periodontal tissue profiles in vivo. Material and Methods: In experiment 1, refractive indices of purified water, porcine gingiva and human gingiva at 1330 nm were determined for the analysis of OCT images of periodontal tissues. In experiment 2, OCT examination was performed in the midlabial apico‐coronal plane of mandibular anteriors in 30 Asian volunteers with healthy gingiva. Sulcus depth was measured on intra‐oral photographs taken during probing. In the OCT images, the gingival, epithelial and connective tissue thickness, and the position of alveolar bone crest were determined and finally, the biologic width was measured. Results: Refractive indices of purified water, porcine gingiva and human gingiva were 1.335, 1.393 and 1.397, respectively. Cross‐sectional images of gingival epithelium, connective tissue and alveolar bone were depicted in real‐time. The sulcular and junctional epithelium could be visualized occasionally. Laser penetration and reflection were limited to a certain depth with an approximate maximal imaging depth capability of 1.5 mm and OCT images of the periodontal structure were not clear in some cases. The average maximal thickness of gingiva and epithelium and biologic width at the mandibular anteriors were 1.06 ± 0.21, 0.49 ± 0.15 and 2.09 ± 0.60 mm, respectively. Conclusion: OCT has promise for non‐invasive observation of the periodontal tissue profile in detail and measurement of internal periodontal structures including biologic width in the anterior region.